Epidemiological characteristics an outbreak of ST11 multidrug-resistant and hypervirulent Klebsiella pneumoniae in Anhui, China - He, Zhien; Xu, Weifeng; Zhao, Hang; Li, Wei; Dai, Yuanyuan; Lu, Huaiwei; Zhao, Liping; Zhang, Changfeng; Li, Yujie; Sun, Baolin (Frontiers in Microbiology, 2022)
Klebsiella pneumoniae has become a primary threat to global health because of its virulence and resistance. In 2015, China reported multidrug-resistant (MDR) and hypervirulent K. pneumoniae (hvKp) isolates. The emergence of MDR-hvKp poses a significant threat to public health. We collected 76 MDR K. pneumoniae isolates from the same hospital, of which there were a total of six MDR-hvKp isolates. We performed multilocus sequence typing (MLST) and capsular typing, whole genome sequencing, comparative genome analysis, and phylogenetic analysis as well as phenotypic experiments, including growth curves, mucoviscosity assay, Galleria mellonella infection model, human whole blood survival, and human neutrophil bactericidal assay to further characterize the samples. We identified six large plasmids carrying extended spectrum β-lactamase (ESBL) genes or carbapenemase genes (blaCTX-M-65, blaKPC-2, blaSHV-12, blaSHV-158), 9 plasmids containing other drug resistance genes, and 7 hypervirulence plasmids carrying rmpA and rmpA2 in ST11 MDR-hvKp isolates. Some of these plasmids were identical, whereas others differed only by insertion elements. In addition, we identified a plasmid, p21080534_1, that carries hypervirulence genes (iucABCD, iutA, rmpA2), a carbapenemase gene (blaKPC-2), and an ESBL gene (blaSHV-12), as well as MDR-hvKp 21072329, which did not carry rmpA or rmpA2, but exhibited hypervirulence and hypermucoviscosity. ST11 MDR-hvKp derived from hypervirulence and multidrug resistance plasmids not only causes significant treatment difficulties, but also represents an unprecedented challenge to public health. Therefore, urgent measures are needed to limit further spread.